Analyzing Vietnam’s textile garment global supply chain with the Revealed Comparative Advantage - Ngoc Quyen Nguyen (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This paper aims to calculate and analyze the Revealed Comparative Advantage index (RCA) of Vietnam’s textile garment industry in the global supply chain by comparing it to other countries, thereby suggesting appropriate solutions.Method — The research uses the calculation method of Revealed Comparative Advantage - RCA. RCA brings up an efficient method to analyze a nation’s comparative advantage based on actual export activity data that were extracted from the TRADEMAP platform.Result — Although Vietnam has many advantages and strong features, the RCA index (1.93) in this study shows that Vietnam's total textile garment supply chain ranks fifth on a worldwide scale, following Bangladesh (10.54), Turkey (3.81), China (2.55), and India. (2.47). The raw materials (RCA 1.65) and fabric production (RCA 1.29) phases are extremely weak, ranking sixth and fourth in the world, respectively. Making garments is the best, ranking third globally and with an RCA of 3.4.Contribution — This research validates the usefulness and feasibility of the RCA calculation approach for analyzing the comparative advantages of Vietnam's textile garment supply chain, which has never been used previously. The research measured and quantified the benefits of Vietnam's textile garment supply chain in order to compare other rivals visibly, so readers can clearly grasp where Vietnam stands on the global textile garment supply chain.